Latex Dipping : Science and Technology - Hill, David M. (De Gruyter, 2019)
Latex products that we use in everyday life have a great impact on health and lifestyle. This book gives a comprehensive overview of how raw materials are prepared for latex manufacture and how they are converted to products by modern latex dipping methods. Tools for how to solve production problems encountered, quality control and how to validate the processes used in the latex industry are thoroughly discussed and described.- Resumé vydavatel